H2SおよびATP補捉作用を有するrepagermanium (Ge-132) はマウスにおけるパクリタキセル誘発性末梢神経障害を抑制する - 中村, 宜司; 関口, 富美子; 川畑, 篤史; 安達, 義史; 島田, 康弘 (日本薬理学会年会要旨集, 2022)
We have reported that the enhanced activity of Cav3.2 T-type Ca2+ channels caused by endogenous H2S participates in the paclitaxel (PCT)-induced peripheral neuropathy (PIPN), and that neuron-derived ATP promotes the PCT-induced macrophage (Mφ) infiltration followed by extracellular release of HMGB1, a damage-associate molecular pattern protein, leading to PIPN development. On the other hand, we have found that repagermanium (i.e. Ge-132), once hydrolyzed into 3-(trihydroxygermyl)propanoic acid (THGP), can trap H2S, in addition to ATP, and inhibit H2S-induced enhancement of Cav3.2 activity and pain. Thus, we evaluated effects of THGP on PIPN in mice. In the mice treated with PCT repeatedly, daily i.p. administration of THGP at 100 mg/kg prevented PIPN development and Mφ accumulation in the sciatic nerves. In Mφ-like RAW264.7 cells, THGP at 10 mM inhibited the cell migration caused by ATP at 0.1 mM, but not extracellular HMGB1 release caused by ATP at 1 mM. Finally, a single i.p. administration of THGP at 100 mg/kg, as well as TTA-A2, a Cav3 inhibitor, at 1 mg/kg, reversed the established PIPN in mice. These data suggest that THGP prevents PIPN development by trapping ATP that promotes PCT-induced perineuronal Mφ accumulation and reverses PIPN most probably by trapping H2S that enhances Cav3.2 activity.